Pengaruh Waktu Kupas dan Volume Kayu Terhadap Produktivitas dan Biaya Pengupasan Kulit Kayu Hutan Alam - Sona Suhartana; Yuniawati Yuniawati (Fakultas Kehutanan Universitas Mulawarman, 2021)
Debarking is the activities in the loading point after bucking. The purpose of debarking is to clean wood from bark and reduce the wood moisture content to be easier for further handling. The research method was carried out by selecting the location of 2 loading points where debarking was done, measuring the debarking time and the log volume, and then analyzing the effect of debarking time and log volume on the productivity of debarking with multiple regression analysis. The results showed that: 1) The average debarking produkctivity in loading point 1 was 21.12 m3/hr an average debarking time of 25.49 minutes and log volume of 9.16 m3; 2) The average productivity of debarking in the second loading point was 20.77 m3/hr with an average debarking time of 19.45 minutes and a log volume of 6.81 m3; 3)The average of debarking cost at loading point #1 is lower than at loading point#2; 4) The resulting regression equation model is Y = 20,931.001 – 49,516.314 X1 + 2.324 X2; and 5)The log volume is significant to debarking productivity, while the debarking time is negative